Instrumentalización de la consulta previa a los pueblos indígenas u originarios, entre lo formal y lo material de su aplicación - Ortega Rojas, Adrián Vinicio (2024)
The following research work is entitled "Instrumentalization of prior consultation with indigenous peoples, between the formal and material aspects of its application", and this contribution is motivated by the legal consequences that have resulted from the lack of materialization of the right to prior consultation of Ecuadorian communities, indigenous peoples, and nationalities. The analysis that has been carried out shows that, despite the fact that the Constitutional Court of Ecuador has issued several pronouncements aimed at determining the importance of consulting indigenous peoples regarding measures that affect their territories, however, due to the ineffectiveness of the National Assembly of Ecuador, these have failed to materialize in a normative adaptation that contemplates the minimum parameters of prior consultation. This has given rise to a scenario that in reality reflects in the discontent of indigenous groups and the need to activate constitutional justice repeatedly in response to actions aimed at exploitation of non- renewable natural resources, which is undoubtedly creating a negative impact on the environment, often irreversible, which can decimate nature's rights and prevent the development of these communities. The following general objective and three specific objectives have been established: to conduct a legal, doctrinal, and jurisprudential analysis of the nature of prior consultation relating to non- renewable natural resources, and to determine how it is utilized in Ecuador; to identify the current regulation for the application of prior consultation; to analyze the relevant jurisprudence issued by the Ecuadorian Constitutional Court on the right to prior consultation; and, as part of the field research to be conducted directed at community members of the Gualel parish, near the Fierro Urco paramo, in Ecuador, it will be determined which regulatory elements are necessary for implementing prior consultation in Ecuador. The following methods were used: deductive, analytical, exegetical, comparative, synthetic and statistical, as well as survey, interview and case study techniques.